Framing of Flood News in The Borneo Post, a Regional Malaysian Newspaper - Li, Ning; Ting, Su-hie (Human Behavior, Development and Society, 2024)
In recent years, climate change and unpredictable weather are causing more frequent severe floods in various areas, but little is understood about how regional newspapers shape public reactions to and preparations for natural disasters. This study investigated the framing of flood news by The Borneo Post, an English-language newspaper circulated in Sarawak, Malaysia. The specific aspects examined were: (a) frequency of thematic and episodic framing of flood events and (b) frame dimensions used in articles. Altogether 76 articles (25,676 words) on floods published by The Borneo Post from 1 January to 31 December 2023 were analysed. All articles were in the episodic frame. The main frame dimension was attribution of responsibility (79%), where authorities act as disseminators and narrators of disaster facts. However, the absence of thematic framing of floods lowers attribution of responsibility to authorities to plan long-term solutions to flooding. The economic consequences frame ranked second (14.5%), emphasising losses suffered. Little attention was given to human interest (3.9%) or conflict (1.3%). There was no morality frame, and 1.3% of articles were fact-filled and did not have an obvious frame dimension. The findings suggest that fact-focused flood reporting lacking the humanity element may not move readers to action.